(untitled) (Economic and Political Thought, 2011)
The article is aimed at systematizing the discussion about the Turkish membership of the European Union. The author presents the difficult historical Turkish route to the European Union which started in the 1950s when the Turkish state joined the North Atlantic Treaty Organization and finished with the accession negotiations initiated in 2005. The subject-matter of the analysis is also an answer to the question about the European roots of Turkey. The author discusses the location of Turkey because the literature of the topic does not explicitly define whether Turkey is in Europe or not. He also wonders whether the absence of Christianity as a major religion in Turkey is an obstacle in the process of European integration and how the Europeans will react to a larger emigration of the Muslim population. As far as the issue of Turkish membership of the European Union is concerned, the key problems are the effects of such accession. The author proposes a thesis that Turkish accession to the European Union will basically strengthen the position of big countries in the voting procedure of the Council of the European Union. However, on the other hand, Turkey will be a big burden for the European budget because it needs many reforms. The article also deals with the issue of substituting the full membership with an idea of privileged membership which Turkey is not going to accept, and the Polish involvement in the process of Turkish accession. A discussion about Turkish accession will continue for many years. Member states’ attitudes towards Ankara’s membership of the European Union differ so much that they may be a barrier impossible to overcome.